2012
DOI: 10.1007/978-3-7091-0956-4_44
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and Temporal Horn Ratio: A Valid and Reliable Index to Determine Ventricular Size in Paediatric Hydrocephalus Patients?

Abstract: Because there is currently no sufficient and prevalent parameter for estimating ventricular size in paediatric hydrocephalus patients by using cranial ultrasound, a new measurement index, called the "frontal and temporal horn ratio", is presented in this study. The advantage of the new quotient is that it can be detected in easily obtainable coronal ultrasound planes. A retrospective analysis of 149 MRIs of young hydrocephalus patients proved the new index to be a promising parameter of ventricular size assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Although volumetric techniques are probably most representative of true ventricular volume, linear measures are primarily used in current clinical practice; 2,15 nonetheless, image analysis techniques used in our study revealed patterns related to ventriculomegaly that may inform future investigations. For instance, enlargement of the subarachnoid space in pediatric patients has been cited as a potential confounder when determining true intracranial volume.…”
Section: Discussionmentioning
confidence: 76%
“…Although volumetric techniques are probably most representative of true ventricular volume, linear measures are primarily used in current clinical practice; 2,15 nonetheless, image analysis techniques used in our study revealed patterns related to ventriculomegaly that may inform future investigations. For instance, enlargement of the subarachnoid space in pediatric patients has been cited as a potential confounder when determining true intracranial volume.…”
Section: Discussionmentioning
confidence: 76%
“…The frontal and temporal horn ratio (the ratio of interventricular distance between the frontal and temporal horns of the lateral cerebral ventricles) is probably the new ultrasonographic index, which can be easily measured on the coronal sonographic section of the brain. The statistical comparison between new frontal and temporal horn ratio and commonly used frontal and occipital horn ratio shows strong linear correlation between both coefficients [300].…”
Section: Morphology Of the Cerebral Ventricles In Pediatric Hydrocephmentioning
confidence: 88%
“…Additionally, MR is an expensive modality and CT could expose the patient to potential adverse effects of radiation. Therefore, US can serve as the best readily available imaging modality for evaluating infants with ventriculomegaly [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of cross-sectional planes is important to neurosurgeons who rely on ventricular size measurements to determine the necessity and timing for surgical interventions. A fronto-temporal horn ratio (FTHR) has been established as a coronal plane analog to the axial FOR [11]. In addition, Radhakrishnan et al [9] found favorable results for interobserver reliability in US-FOR measurements modified for the coronal plane in children with ventriculomegaly; their study also showed a good correlation with MR-FOR measurements.…”
Section: Introductionmentioning
confidence: 99%